SYSTEMATIC LITERATURE REVIEW (SLR): DISEASE DETECTION IN MELONS USING DIGITAL IMAGE PROCESSING - Frieyadie Frieyadie (Kresnamedia Publisher, 2020)
Abstract¾Systematic Literature Review (SLR) is a technique used in this study that is used to study techniques for identifying leaf diseases using digital images as a basis for obtaining an understanding of disease identification techniques in melon leaves with digital images. Based on data from the Central Statistics Agency for the last 3 years from 2017-2019, melon production has increased considerably. Melon production data in 2017 was 92.43 tons, in 2018 was 118,708 and in 2019, overall melon production was 122,105 tons collected from 34 provinces in Indonesia. The problem that is often encountered in melon cultivation is the presence of plant pests that can harm and not maximize the yields of farmers. Several viruses cause mosaic disease that infects Cucurbitaceae plants, namely Cucumber aphid borne yellows virus (CABYV), Cucumber green mottle mosaic virus (CGMMV), Cucumber mosaic virus (CMV), Papaya ringspot virus (PRSV), Squash mosaic virus (SqMV), Squash leaf curl virus (SLCV), Watermelon mosaic virus (WMV). Information technology has now developed to be able to manage digital image data to identify problems faced by farmers. Several classification methods that can be used to answer problems include SVM, Artificial Neural Network, Decision Tree, Convolutional Neural Network.